Coping strategies available for women living with HIV/AIDS experiencing intimate partner violence in the Singida region, Tanzania - Kosia, Agnes L.; Frumence, Gasto; Nyamhanga, Tumaini; Semakafu, Ave Maria; Kakoko, Deodatus (International Journal Of Community Medicine And Public Health, 2021)
Background: Intimate partner violence is a major public health problem in Tanzania, yet little is known about the coping strategies among women living with HIV/AIDS who experiencing IPV. The objective of the study was to explore the coping strategies employed by women living with HIV/AIDS experiencing IPV who attended care and treatment services in the Singida region. Methods: A qualitative phenomenology study design was performed in which data were collected through in-depth interviews with 35 women living with HIV/AIDS who also experienced IPV. Content analysis was used to analyse the data. Results: We found that women living with HIV/AIDS experienced IPV used family members, such as their mothers, sisters, and brothers as a coping mechanism to express their pains. Spiritual leaders counselled them spiritually and psychologically and they were advised on how to live with their violent partners. Other coping mechanisms included reporting to the police and the legal system, and the use of support groups. Through support groups, they obtained relief from depression, loneliness, isolation, stigma and discrimination. Conclusions: This study concludes that coping mechanisms helped women living with HIV/AIDS to reduce the stress associated with HIV/AIDS and intimate partner violence. The government of Tanzania should strengthen policies related to IPV and HIV/AIDS among all women in Tanzania. Moreover, local government authorities should build safe homes for all survivors of intimate partner violence throughout the country.